The influence of the addition position of cellulose nanofibers on the crystalline and mechanical properties of carbon fiber-reinforced polypropylene composites. Issue 9 (2nd September 2022) - Matsumoto, Koki; Takemura, Kenichi
ABSTRACT: The introduction of nanofillers into conventional microsized fiber-reinforced plastic composites has great potential to improve the fracture toughness and crystalline properties of composites, especially for semicrystalline thermoplastic polymers. Although the selective reinforcement is possible by nanofiller addition, the influence of the addition position of nanofillers on the mechanical properties and crystalline properties still has not been revealed. In this work, the cellulose nanofibers (CNFs) as the secondary filler were added (i) into a polypropylene (PP) matrix by a melt-mixing process and (ii) onto a carbon fiber (CF) surface by a dip-coating process in a CF-reinforced PP composite. By focusing on the transcrystals surrounding CFs, which enable improvement of the interfacial strength, the crystalline properties and mechanical properties were investigated through polarized optical microscopy, differential scanning calorimetry, X-ray diffraction, and 3-point bending tests in this study. We revealed that (i) CNF addition into the PP matrix disturbed the transcrystallization surrounding CFs and that the mechanical properties slightly decreased. Conversely, (ii) CNF addition onto the CF surface promoted transcrystallization surrounding the CF, and the flexural yield strength and modulus significantly improved by a maximum of 30% and 63%, respectively. GRAPHICAL ABSTRACT: uf0001